GAMIFICATION SEBAGAI INOVASI PEMBELAJARAN DIGITAL: ANALISIS LITERATUR TENTANG DAMPAKNYA TERHADAP KETERLIBATAN BELAJAR SISWA - Muhammad Hafi Badali; Novi Handayani; Putri Normeiliani; Zaliha; Ahmad Suriansyah; Wahdah Refia Rafianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the application of gamification as an innovation in digital education and its impact on student learning engagement at the elementary school level. The method used was a literature review, which included an analysis of seven recent scientific articles related to gamification elements, motivation to learn, and student engagement in digital learning contexts. The analysis was conducted through identifying themes such as the use of points, badges, levels, challenges, leaderboards, avatars, and the use of digital media such as Quizizz, Wordwall, and interactive Canva. The review results indicate that gamification can consistently increase intrinsic and extrinsic motivation, active participation, concentration, and self-confidence in students. Learning becomes more enjoyable, interactive, and positively competitive, resulting in students being more responsive to instructions and engaged cognitively, emotionally, and socially. Furthermore, several studies have also shown improved learning outcomes after the implementation of gamification compared to traditional learning methods. These findings confirm that gamification is an effective and relevant pedagogical approach in this digital age and can be implemented as a sustainable learning strategy to improve the quality and engagement of students in elementary schools.